2016
DOI: 10.1007/s40596-016-0487-1
|View full text |Cite
|
Sign up to set email alerts
|

The Association Between a Sense of Calling and Physician Well-Being: A National Study of Primary Care Physicians and Psychiatrists

Abstract: Physicians who reported that medicine was a calling may be experiencing higher levels of career satisfaction, more durable clinical commitments, and resilience from burnout. Though physicians may differ on their understanding of the concept of calling in medicine, this study highlights an important factor that should be investigated further when assessing long-term workforce retention in the fields of primary care and psychiatry.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
66
1
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 72 publications
(70 citation statements)
references
References 35 publications
2
66
1
1
Order By: Relevance
“…47,48 For example, a study among PCPs and psychiatrists found that those with a sense of calling appear to be more resistant to burnout. 36 However, it is noteworthy that career and life satisfaction did not increase even further once a person reported ≥7.5 personally rewarding hours per day. This finding implies that excessive work hours may have a negative association with well-being, even when those hours are perceived as personally rewarding.…”
Section: Discussionmentioning
confidence: 93%
See 2 more Smart Citations
“…47,48 For example, a study among PCPs and psychiatrists found that those with a sense of calling appear to be more resistant to burnout. 36 However, it is noteworthy that career and life satisfaction did not increase even further once a person reported ≥7.5 personally rewarding hours per day. This finding implies that excessive work hours may have a negative association with well-being, even when those hours are perceived as personally rewarding.…”
Section: Discussionmentioning
confidence: 93%
“…However, very few empirical studies have examined intrinsic factors, though more recent studies have begun to focus on a sense of calling. 31,36 For example, one study has found that sense of calling is associated with PCPs' satisfaction in treating certain conditions such as smoking, alcoholism, and obesity. 31 Our study suggests that focusing only on extrinsic motivators neglects other determinants of physician wellbeing.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Because physicians are more than technicians, 15 their role as healers partly relies on their moral and spiritual development and character. 16,17 Thus, physicians’ R/S are associated with risk of burnout, 18 moral distress, and compassion fatigue. 1921 Practices of self-care, including self-awareness of the physician’s own needs in conjunction with patient needs, support physicians’ well-being.…”
Section: Introductionmentioning
confidence: 99%
“…Yoon et al surveyed by mail a national sample of approximately 1500 primary care physicians and 512 psychiatrists, with a response rate of 63-64% [6]. The primary finding was that a "sense of calling" tended to correlate with "well-being."…”
mentioning
confidence: 99%